Uptake, adverse effect, and associated factors of COVID-19 vaccine among those living with human immunodeficiency virus, at Bole sub-city health facility Addis Ababa, Ethiopia - Sendu Seid; Teferi Gebru Gebremeskel (Human Vaccines & Immunotherapeutics)
COVID-19 vaccination in African people living with human immunodeficiency virus remains understudied, with limited research in Ethiopia that fails to consider contextual differences. To assess uptake, adverse effects, and associated factors of COVID-19 vaccine among PLWHA in Addis Ababa, Ethiopia, 2022. An institutional cross-sectional study design was employed among 404 participants. Sample selected by systematic random sampling technique. Descriptive and inferential statistical analyses were carried out. Finally, results were presented using Crude Odd Ratio, Adjusted Odd Ratio, and 95% Confidence Interval. Result: Out of all participants, 79% (314) received at least one dose of any type of COVID-19 vaccine, with varying percentages taking one (29.3%), two (50.3%), and three (20.4%) doses of the vaccine. Being knowledgeable (moderate and good) (AOR = 0.06, 95% CI: 0.01, 0.5) and medium attitude (AOR = 1.1, 95% CI: 0.7, 1.3) had a statistically significant association with the uptake of the COVID-19 vaccine. The prevalence of adverse events was 27.8% (110). More than three-quarters of participants were vaccinated for the COVID-19 vaccine. Moderate knowledge and medium attitude have a significant association with the uptake of the COVID-19 vaccine. Nearly a quarter of participants experienced adverse events related to COVID-19. Continued efforts are essential to overcome barriers to achieving full vaccination coverage for the most vulnerable in low-income countries. Addressing hesitancy, monitoring side effects, and implementing effective communication and strategies are crucial for widespread COVID-19 vaccination and public health safety in these regions.